Geochronological and Stable Isotope Evidence for Widespread Orogenic Gold Mineralization from a Deep-Seated Fluid Source at ca 2.65 Ga in the Laverton Gold Province, Western Australia - Salier, B.; Groves, D.; McNaughton, Neal; Fletcher, Ian (Society of Economic Geologists Inc, 2005)
Many gold deposits in the Laverton greenstone belt, in the northeast of the Eastern Goldfields province of the Yilgarn craton, are located adjacent to, or hosted by, granitoids. This has led to controversy over whether the granitoids provided the auriferous fluids from which the deposits formed or were structural traps controlling the siting of the gold deposits. New regional-scale stable isotope data, combined with robust geochronologyon several deposits, resolves this controversy in the Laverton greenstone belt. The median S, C, and O isotope compositions of ore and gangue minerals from nine different gold deposits in the Laverton greenstone belt fall in a very narrow range. The only exceptions to this are the more negatived 34S values of ore sulfides at the Jupiter gold deposit, which were most likely caused by pre existing highly oxidized host rocks and the more negative d13C values of ore carbonate at deposits with reduced black shale hostrocks. Redox conditions and mineralization temperatures for all gold deposits in the Laverton greenstone belt are broadly similar. Therefore, the lack of variation in the isotopic compositions of ore and gangue minerals is consistent with their deposition from a similar ore fluid. There is no convincing evidence to indicate that more than one ore fluid was involved in deposition of gold deposits within the Laverton greenstone belt, although the data do not uniquely define the source of the ore fluid (e.g., whether it was proximal or distal). SHRIMP U-Pb dating of gold-related monazite and xenotime provides a temporal framework for gold mineralization in the Laverton greenstone belt. Synmineralization phosphates have ages of 2650 7 Ma at MountMorgans, 2649 11 Ma at Jubilee, 2657 21 Ma at Jupiter, and probably 2653 6 Ma at Granny Smith. The similarity in age of these four deposits, as well as previously published ages for the Wallaby (2650 5 Ma) and Sunrise Dam and/or Cleo deposits (2654 8 Ma), places three major constraints on the source of auriferous fluids in the Laverton greenstone belt. First, the Wallaby and, most likely, the Granny Smith gold deposits arenot the same age as adjacent granitoids, ruling out the exposed granitic rocks as a proximal magmatic fluid source. Second, the broadly synchronous timing of gold mineralization on a camp scale provides evidence that the deposits have a similar genesis. Third, the range of ages of the gold deposits is not as great as that of the granitoids postulated to be their source. Magmatic activity that has been invoked as the source of ore fluids by various workers is related to several geochemically distinctive granitoid suites that are diachronous over several tens of millions of years in the Laverton greenstone belt and the wider Eastern Goldfields province. In contrast, the consistent age of gold mineralization in the Laverton greenstone belt supports a single fluid source, as implied by the isotope geochemistry. It is concluded that all studied deposits are orogenic gold deposits with a distal and deep source.